Introduction to the Audiological Evaluation: Case-Based Applications to Patients with Skull Base Disease - Dumanch, Kelsey A.; Poling, Gayla L. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objectives To provide an introduction to the role of audiological evaluations with special reference to patients with skull base disease.Design Review article with case-based overview of the current state of the practice of diagnostic audiology through highlighting the multifaceted clinical toolbox and the value of mechanism-based audiological evaluations that contribute to otologic differential diagnosis.Setting Current state of the practice of diagnostic audiology.Main Outcome Measures Understanding of audiological evaluation results in clinical practice and value of contributions to interdisciplinary teams to identify and quantify dysfunction along the auditory pathway and its subsequent effects.Results Accurate auditory information is best captured with a test battery that consists of various assessment crosschecks and mechanism-driven assessments.Conclusion Audiologists utilize a comprehensive clinical toolbox to gather information for assessment, diagnosis, and management of numerous pathologies. This information, in conjunction with thorough medical review, provides mechanism-specific contributions to the otologic and lateral skull base differential diagnosis.
Keywords: hearing; assessment; hearing loss; audiology; normal hearing